قياس القيمة العادلة للأسهم العادية باستعمال نموذج مضاعف الربحية : دراسة تطبيقية في المصارف العراقية الخاصة المدرجة في سوق العراق للأوراق المالية - عبدالزهرة، كرار سليم; طلب، حسنين راغب (جامعة الكوفة - كلية الإدارة والاقتصاد, 2013)
يهدف البحث إلى توضيح مفهوم القيمة العادلة ومبررات استخدامها، واستعراض الطرق الممكنة لقياس القيمة العادلة للأسهم، فضلا عن بيان إمكانية قياس القيمة العادلة للأسهم العادية باستعمال نموذج مضاعف الربحية. \ ولتحقيق هدف البحث فقد تم اختبار ذلك النموذج بالتطبيق على المصارف العراقية الخاصة المدرجة في سوق العراق للأوراق المالية للفترة من ٢٠٠٩ -٢٠١٢. \ وقد تم استخدام برنامج الحزمة الإحصائية SSPS في حساب متغيرات النموذج المتمثلة بالانحراف المعياري والارتباط الخطي البسيط، وقد توصل البحث إلى إمكانية قياس القيمة العادلة لأسهم المصارف العراقية الخاصة باستخدام النموذج المذكور. \ وانطلاقا من نتائج البحث يوصي الباحثون بضرورة قيام المصارف العراقية وسوق العراق للأوراق المالية بقياس وإظهار القيمة العادلة للأسهم في التقارير التي يصدرونها، وضرورة قيام الجهات المنظمة لعمل المهنة المحاسبية في العراق بإصدار معيار أو قاعدة محاسبية محلية تتعلق بالقيمة العادلة للأسهم لضرورة ذلك في تشجيع الاستثمار وتوظيف رؤوس الأموال في الوحدات الاقتصادية العراقية. The research aims to clarify the concept of fair value and justification for their use ، and review possible ways to measure the fair value of the shares ، as well as show the possibility of measuring the fair value of the ordinary shares using a multiplier profitability model . To achieve the objective of this research has been tested that model application on the Iraqi private banks listed on the Iraq Stock Exchange for the period from 2009-2012. The statistical software package SSPS used in the calculation of form variables of the standard deviation and simple linear correlation ، The research found to the possibility of measuring the fair value of the shares of Iraqi private banks using the Model mentioned . \ Proceeding from the results researchers recommend the need for the Iraqi banks and the Iraqi market for securities measuring and demonstrating the fair value of the shares in the reports that they issue ، and the need for regulators to make the profession of accounting in Iraq issued a standard or base accounting local related to fair value of the shares it necessary to encourage investment and employment of capital money in the Iraqi economic units .
777084 810969
Keywords: الأسهم -- أرباح الأسهم -- البنوك -- المعاملات -- العراق